Self-Concept, Reference Group and Cosmetic Purchase Decision Among Early Adult Man in Yogyakarta - Lia Fajrina Binuril Hidayati; Miftahun Ni'mah Suseno (Psikostudia : Jurnal Psikologi, 2025)
Cosmetics are only for women to use? That's not the era anymore. Cosmetics were originally only used and intended for women. With the development of the times, now men are starting to take care of themselves by using cosmetics. The influence of self-concept on the needs of the body, skin and appearance and reference groups such as friends, family and the internet make them decide to buy and use cosmetics. This study aims to determine the relationship between self-concept and reference groups with the decision to purchase cosmetics in early adult men. The type of research used is quantitative approach. The subjects in this study were 185 early adult male cosmetic users who live in Yogyakarta. The research hypothesis is that there is a positive relationship between self-concept, reference groups and cosmetic purchasing decisions in early adult men. Data were collected using a purchase decision scale developed from the theory of Peter & Olson, a self-concept scale according to the theory of Calhoun and Acocella, and a reference group scale, developed from Setiadi's theory. The results of the regression analysis showed R = 0.56 and F = 5.01 with a significance of 0.03 (p < 0.05). The results showed that there was a positive relationship between self-concept and reference groups with cosmetic purchase decisions for men in Yogyakarta. Self-concept and reference groups make an effective contribution of 31% to purchase decisions with details of reference groups having an effect of 29% and self-concept by 2%. This shows that the reference group has a greater influence than self-concept in shaping cosmetic purchase decisions.Kosmetik hanya digunakan wanita? Sudah bukan jamannya lagi. Kosmetik pada awalnya hanya digunakan dan ditujukan untuk wanita. Seiring berkembangnya zaman, kini para pria mulai merawat diri dengan menggunakan kosmetik. Pengaruh konsep diri terhadap kebutuhan tubuh, kulit dan penampilan serta referensi kelompok seperti teman, keluarga dan internet membuat mereka memutuskan untuk membeli dan menggunakan kosmetik. Penelitian ini bertujuan untuk mengetahui hubungan antara konsep diri dan kelompok acuan dengan keputusan pembelian kosmetik pada pria dewasa awal. Jenis penelitian yang digunakan adalah pendekatan kuantitatif. Subjek dalam penelitian ini adalah 185 orang pengguna kosmetik pria dewasa awal yang berdomisili di Yogyakarta. Hipotesis penelitian adalah terdapat hubungan positif antara konsep diri, kelompok acuan dengan keputusan pembelian kosmetik pada pria dewasa awal. Pengumpulan data menggunakan skala keputusan pembelian yang dikembangkan dari teori Peter & Olson, skala konsep diri menurut teori Calhoun dan Acocella, dan skala kelompok acuan yang dikembangkan dari teori Setiadi. Hasil analisis regresi menunjukkan R = 0,56 dan F = 5,01 dengan signifikansi 0,03 (p < 0,05). Hasil penelitian menunjukkan terdapat hubungan positif antara konsep diri dan kelompok acuan dengan keputusan pembelian kosmetik pada pria di Yogyakarta. Konsep diri dan kelompok acuan memiliki sumbangan efektif sebesar 31% terhadap keputusan pembelian dengan rincian kelompok acuan berpengaruh sebesar 29% dan konsep diri sebesar 2%. Hal ini menunjukkan bahwa kelompok referensi mempunyai pengaruh lebih besar daripada konsep diri dalam membentuk keputusan pembelian kosmetik.